Fungsi Komunikasi Antarbudaya dalam Kepariwisataan - Neni Efrita (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2015)
Tourism role in the economic development seen from the figures always show a statistically significant increase. But tourism is not only economic issues but also social problems of culture, politics and so on. Tourism is a multi-complex systems with various aspects are interrelated and influence each other among fellow. In addition to acting as economic driver tourism activities also provide opportunities to create business field. nature preserve, not destroy the environment. This development is characterized by an increasing number of tourist arrivals and tourist arrivals are expected to continue increasing frequency. Developing tourism because of the movement of people in search for something that did not already know, exploring a new area, looking for a change of atmosphere or to get a new experience in the goal area. Tourists who come to the tourist destination partly driven by curiosity to know, to know or to learn the culture of the region and local communities. During his stay in the tourist destination will definitely interact with people directly involved with servicing the needs of tourists. Interaction between intercultural in tourism activity is strongly influenced by socio-cultural systems of both parties. Besides interaction between cultures that they do have a function - for their own function, there to express identity / social, social integration, to increase knowledge and others. Intercultural communication in tourism is very unique, because every communication activities performed its function will vary according to the communication situations that occur